(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
This paper considers how there is an inherent unsettledness and instability in the phenomenology of seeing. Its exploration concerning light, visibility and spatiality is grounded in the post-Husserlian phenomenology of Merleau-Ponty and informed by the later hermeneutic inquiries of Heidegger. The paper also draws on the author’s own experience of visual change and disturbance.